An investigation of compressed air energy storage methods - Kantharaj, Bharath (2019)
This thesis broadly concerns the analysis of air storage methods within Compressed Air Energy Storage (CAES) systems. In a typical CAES system, pressurised air generated by electrically driven compressors is first stored in appropriate containments. During times of need, energy from the high-pressure air is recovered by withdrawing it from the containment and subsequently expanding it in appropriate machinery. Since the most established method of air storage for commercial CAES applications today is in underground salt caverns, the thesis begins by analysing this technology. In particular, the thesis focuses on formulating a loosely coupled thermomechanical finite element model to predict the response of such caverns subjected to high-frequency cycling of compressed air. It is found that whilst the temperature variations are confined to a small region near the wall of the cavern, its effect on the resulting stress field is significant, especially when the rate of change of temperature is negative causing the resulting stresses to be tensile in nature. The structural stability of the cavern is investigated using two separate failure criteria which suggest that when the internal air pressure is minimum and change in temperature is maximum, the cavern is more susceptible to failure. Recognising the fact that underground salt caverns are geologically constrained and thus might present an obstacle to widespread CAES deployment, two novel air storage methods have been proposed. The first is a hybrid compressed air-liquid air energy storage system whose thermodynamic effectiveness is analysed. In this system, the energy storage capacity of compressed air is extended by supplementing the system with energy dense, geologically unconstrained, liquid air storage. The notional system consists of a compressed air store, liquid air store and associated machinery to transform between the two states of air. It is found that a maximum roundtrip storage efficiency of approximately 50% could be achieved, where the roundtrip efficiency refers to the overall performance of converting compressed air to liquid air and back, but before conversion to and from electricity. The second is a rigid underwater containment for storing compressed air, whose structural behaviour during the transaction of pressurised air is investigated. Using the finite element method, preliminary analysis is conducted on rigid wall vessels, where it is shown that non-trivial bending loads exist in the shell of the containment. Past research on flexible wall vessels is documented and contrasted with rigid wall vessels. Underwater environments offer significant advantages to a CAES system in terms of reduced load carrying requirements of the vessel due to the natural hydrostatic pressure restraint, and constant pressure operation which in turn enables more efficient power recovery. However, it is noted that the manufacturing and deployment of underwater vessels play a crucial role, especially at large scales. Since the air storage options investigated are diverse in terms of geographical locations, scale of system, application landscape and technological maturity, a short chapter investigates the capital cost of these air storage systems. Both existing cost data as well as bottom-up estimation methods using cost correlations are employed in deriving the potential total and specific (per unit of stored exergy) costs. It is found that the underground air storage option is the most competitive at £9/kWh, underwater storage option (in rigid vessels) ranks second at £58/kWh and the hybrid storage option is the least competitive at £342/kWh. It is worth noting, however, that both the hybrid and underwater air storage options are novel and their competitiveness can be expected to improve as their technology readiness levels improve. Furthermore, the hybrid air storage option, whilst relatively unattractive on cost, is the least geologically-constrained option and intended for small-to-medium scale applications. Therefore, some parties (e.g. remote microgrids) may be willing to pay a premium on this system in exchange for flexibility in system locatability and scale. Finally, techno-economic and financial analysis of energy storage systems coupled with renewable generators is carried out to gain insight into the commercial viability of a CAES system participating in the energy market today. A rolling-planning optimal scheduling algorithm is developed to maximise profits of a wind power generator coupled with an underground CAES system (since it offers the least cost of storage) from its participation in the wholesale energy market. Various technical parameters are considered in the problem formulation, including the facility to incorporate energy leakage and energy capacity degradation, all within a purely linear optimisation framework. Whilst the proposed wind-CAES system does not produce a positive return on investment today, it is observed that managing the imbalance of the wind generator captures significant value, and stacking revenue sources increases the overall short-term revenue of the system. Furthermore, it is found that managing the imbalance of the renewable generator also reduces the cycling, or wear and tear, of the energy storage system, thereby prolonging its lifetime.